Bioinspired Construction of Artificial Cardiac Muscles Based on Liquid Crystal Elastomer Fibers. Issue 1 (23rd September 2021) - Wang, Yunpeng; Liao, Wei; Sun, Jiahao; Nandi, Rajib; Yang, Zhongqiang
Abstract: Human muscles, including skeletal, smooth, and cardiac muscles, are able to perform diverse deformations and execute complex biofunctions stimulated by nerve signals. Similarly, liquid crystal elastomer (LCE), which can respond to external stimuli with large and reversible deformations, demonstrates superior advantages to mimic nature muscles to fabricate artificial muscles. Till now, LCE has been utilized to simulate deformations and related functions of skeletal and smooth muscles. However, limited by the existing fabrication strategy, employing LCE to mimic the motion of cardiac muscles and further realizing the structure‐determined pumping functions, is still an open challenge. Learning from the specific spatial arrangements and synergistic actuation of cardiac muscle fibers within human heart, a simple and general strategy to construct artificial cardiac muscles with LCE fibers is proposed. In this work, LCE fibers with similar modulus and actuation behavior to muscle fibers are fabricated and spatially arranged in biological architectures as cardiac muscle fibers. As a result, artificial cardiac muscles are constructed and are able to perform simultaneous contraction and torsion motions, realizing heart‐pumping functions. This general strategy should be also applicable for other smart materials to conduct challenging tasks. Abstract : Bioinspired by the spatial alignment of cardiac muscle fibers within human heart, artificial cardiac muscles are constructed by arranging liquid crystal elastomer (LCE) fibers in a biomimetic architecture. The obtained artificial cardiac muscles demonstrate simultaneous contraction and torsion, possessing reliable pumping functions as natural heart. This bioinspired strategy enables LCE as artificial muscles to perform versatile functions towards soft robots.